2007
DOI: 10.1007/s00467-007-0557-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Henoch-Schönlein purpura nephritis treated with long-term immunosuppression

Abstract: This retrospective study investigated the outcome of 27 children (19 male) with Henoch-Schönlein purpura nephritis (HSN) of International Study of Kidney Disease in Children (ISKDC) grade 3b or higher treated with long-term immunosuppressive therapy in a single centre over a 10-year period. The mean age at presentation was 9.7 years. The median estimated glomerular filtration rate (eGFR) was 91.3 ml/min per 1.73 m(2), with the median urine protein creatinine ratio (UP:UC) 556 mg/mmol. The treatment protocol co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 24 publications
(37 reference statements)
4
31
1
2
Order By: Relevance
“…Shenoy et al found 15% patients progressed to ESRD and persistent renal abnormality with daily steroid and cyclophosphamide for 8-12 weeks followed by azathioprine and alternate day steroid for 8-12 weeks in severe form of HSP nephritis. 41 Good results obtained from more aggressive therapeutic regimen consisted with 3 Methyl Prednisolone(MP) pulses followed by 6 months course of prednisolone, depyridamole and 3 month course of cyclophosphamide with >60% complete remission by Oner et al 42 Other reported studies with multi drug therapy supported this result. [43][44][45][46] The randomized controlled study by Kawasaki et al showed combination of MP + urokinase pulses with cyclophosphamide was more effective than MP+urokinase pulses without cyclophosphamide in patients with>50% crescents.…”
Section: Treatment Of Hspnsupporting
confidence: 65%
“…Shenoy et al found 15% patients progressed to ESRD and persistent renal abnormality with daily steroid and cyclophosphamide for 8-12 weeks followed by azathioprine and alternate day steroid for 8-12 weeks in severe form of HSP nephritis. 41 Good results obtained from more aggressive therapeutic regimen consisted with 3 Methyl Prednisolone(MP) pulses followed by 6 months course of prednisolone, depyridamole and 3 month course of cyclophosphamide with >60% complete remission by Oner et al 42 Other reported studies with multi drug therapy supported this result. [43][44][45][46] The randomized controlled study by Kawasaki et al showed combination of MP + urokinase pulses with cyclophosphamide was more effective than MP+urokinase pulses without cyclophosphamide in patients with>50% crescents.…”
Section: Treatment Of Hspnsupporting
confidence: 65%
“…As already mentioned, crescents are much more often seen in HSPN than in IgAN, and their number is related to the severity of clinical signs and to the prognosis of HSPN in most series (16,17,(53)(54)(55)(56)(57)(58)(59)(60). They are frequently seen in association with capillary wall destruction and endocapillary cell proliferation (33).…”
Section: Crescent Formationmentioning
confidence: 97%
“…Renal involvement occurs less frequently in children than adulthood (Yang et al, 2005;Pillebout et al, 2002). The incidence of nephritis in patients with Henoch-Schönlein purpura has been reported to be 15-62% with an estimated annual incidence of 20.4 per 100,000 children (Gardner-Medwin et al, 2002;Shenoy, Bradbury, et al 2007;Bogdanovic, 2009). The overall incidence of Henoch-Schönlein purpura nephritis and the severity of HenochSchönlein purpura nephritis in patients between 1987 and 1997 were similar to those in children between 1998 and 2008 and the number of patients with severe Henoch-Schönlein purpura nephritis has not decreased (Kawasaki et al, 2010).…”
Section: Incidencementioning
confidence: 99%